Analysis of Critical Thinking Skills Students of Sanata Dharma University Through LAVA LAMP Experiments - Pareza, Wintan; Pratiwi, Wizziah (Jurnal Tonggak Pendidikan Dasar : Jurnal Kajian Teori dan Hasil Pendidikan Dasar, 2023)
This study aims to describe the analysis of the implementation of learning critical thinking skills for Sanata Dharma University students through the LAVA LAMP experiment. This study uses a qualitative approach with the type of experimental research. Data from this study were obtained through participatory observation, through interviews with supervisors, and through student work, as well as documentation to support student work. The results showed that the researchers efforts were in using the LAVA LAMP experiment to improve the critical thinking skills of university students Sanata Dharma: The research results show that the researchers' efforts in using the LAVA LAMP experiment to improve the critical thinking skills of Sanata Dharma University students: focusing questions 10 % with category good, ask and answer questions that require explanation 20 % with category very good, observe and consider the results of observations 20 % very good, carry out deductions and assess the results of the deduction 10 % with category good, doing induction 10 % with category good, define terms and consider definitions using appropriate criteria 10 % with category good, identify assumptions 10 % with category very good, and integrate with others 10 % with category good.